Solve for x -10x+9=-9(x-1)

Math
-10x+9=-9(x-1)
Simplify -9(x-1).
Tap for more steps…
Apply the distributive property.
-10x+9=-9x-9⋅-1
Multiply -9 by -1.
-10x+9=-9x+9
-10x+9=-9x+9
Move all terms containing x to the left side of the equation.
Tap for more steps…
Add 9x to both sides of the equation.
-10x+9+9x=9
Add -10x and 9x.
-x+9=9
-x+9=9
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Subtract 9 from both sides of the equation.
-x=9-9
Subtract 9 from 9.
-x=0
-x=0
Multiply each term in -x=0 by -1
Tap for more steps…
Multiply each term in -x=0 by -1.
(-x)⋅-1=0⋅-1
Multiply (-x)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1x=0⋅-1
Multiply x by 1.
x=0⋅-1
x=0⋅-1
Multiply 0 by -1.
x=0
x=0
Solve for x -10x+9=-9(x-1)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top